(untitled) (Journal of history, 2020)
The Kazakh laws originate from Turkic times, and were enriched by the legal practices and cultures of other peoples. Secondly, Kazakh laws borrowed and interpreted adapting to their needs the best samples and models of legal cultures of other peoples. Customary law was designed to address the solution of the complex needs of Kazakh society. Within various historical periods the legal systems aimed to regularize relations between and within nomadic states, have much in common. State structure of Kazakh khanate, system of political governance, legal relations, cultural evolutions originate from early times. Tribal confederations and their legal practices left a rich legacy for Kazakh nomadic society. Key words: customary,law, political, tradition, society.